2017
DOI: 10.1007/s12098-017-2473-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Low Fidelity Manikins for Learning High Quality Chest Compressions

Abstract: Low fidelity manikins are useful for training CPR in sequential manner but fail to impart quality of chest compressions as per AHA recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Therefore, the evaluation of chest compression and ventilation depended on the subjective judgment and sensations of the instructor, and there is a limit to the evaluation of CPR and accurate and consistent feedback. Although it is difficult to conduct training in various scenarios, the recently introduced high-performance mannequin is developing into a form that can accurately record the parameters and numbers of chest compressions and ventilations related for standardized CPR [ 22 ]. Previous studies recommend using a device that records values such as chest compression depth and speed and provides immediate feedback [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of chest compression and ventilation depended on the subjective judgment and sensations of the instructor, and there is a limit to the evaluation of CPR and accurate and consistent feedback. Although it is difficult to conduct training in various scenarios, the recently introduced high-performance mannequin is developing into a form that can accurately record the parameters and numbers of chest compressions and ventilations related for standardized CPR [ 22 ]. Previous studies recommend using a device that records values such as chest compression depth and speed and provides immediate feedback [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 also shows that all respondents had never received CPR training before and had never performed CPR directly on a victim, meaning that the CPR training using a CPR pillow was quite good in transferring knowledge to respondents. Low-fidelity manikins help teach CPR sequentially but fall short of imparting the standard of chest compressions as recommended by the AHA (American Heart Association) (26). However, studies have indicated that low-fidelity resuscitation simulation sessions may establish better muscle memory and reinforce skills more effectively than high-fidelity simulations (26) Ultimately, all CPR training for laypeople is to increase the number of CPR bystanders.…”
Section: Discussionmentioning
confidence: 99%
“…Low-fidelity manikins help teach CPR sequentially but fall short of imparting the standard of chest compressions as recommended by the AHA (American Heart Association) (26). However, studies have indicated that low-fidelity resuscitation simulation sessions may establish better muscle memory and reinforce skills more effectively than high-fidelity simulations (26) Ultimately, all CPR training for laypeople is to increase the number of CPR bystanders. This will also increase the likelihood that OHCA victims will be given immediate and timely CPR properly and correctly.…”
Section: Discussionmentioning
confidence: 99%